Gender Politics in Question: A Comparative Study of Edna O'Brien and Li Ang. Issue 4 (8th August 2022) - Chang, Hawk
ABSTRACT: For centuries women have been subordinated, repressed, and intimidated in different ways. However, women in the contemporary world are trying to reclaim their natural rights. Ireland is a complex case, because in the wake of nationalism, Catholicism, and some other socio-historical conventions, Irish women's movements were forced into the background until the last decades of the 20th century. Accordingly, Irish women have been constrained and daunted by the male discourses of nation, religion, and gender. Intriguingly, women in Taiwan have also been overburdened with pressures related to its unique political, social, and cultural legacies over the past few centuries. However, an increasing number of Taiwanese women have attempted to undo the patriarchy-driven phobia imposed on them to secure and consolidate their female identity. The traditions and transformations of women in both countries are well represented in works by Edna O'Brien and Li Ang. This paper is a comparative study of women in O'Brien's and Li's fiction. The focus is on investigating the ways in which women are subordinated in different historical and socio-cultural milieus, exploring how women react and fight against patriarchal discourses, and discussing the meanings and implications relevant to both writers and their fiction.